Pollen analysis of honey samples collected from various regions of Peninsular Malaysia - Kirthiga Selvaraju (2015)
Melissopalynological studies were carried out on 15 honey samples collected from various states of Peninsular Malaysia. These states were Kedah, Perak, Melaka, Negeri Sembilan, Johor and Penang. The objective of this study was to identify the different types of pollen in honey samples besides determining their floral sources, geographical and botanical origin of local Malaysian honeys. Acetolysis method using Potassium hydroxide solution was done on the honey samples and the pollen were viewed under microscope for identification in terms of morphology and to classify them according to their families and species. The percentage of abundance of pollen was calculated in each honey sample besides identifying the dominant pollen. 60 types of pollen were discovered from 34 different families. From the analysis, 4 honey samples were unifloral and the rest were multifloral. Among the unifloral honeys were the samples from Kubang Pasu and Padang Terap (Kedah), Jasin (Melaka) and Gertak Sanggul (Penang). Jacaranda obtusifolia was the predominant pollen in the honey sample from Kedah. Hevea brasiliensis was dominant in the sample from Jasin, Melaka. As for Gertak Sanggul district of Penang, the dominant pollen was Cucumis melo. The important marker pollen which distinguished Malaysian honey from imported foreign honeys were Cocos nucifera and Elaeis guineensis which occurred in most of the local honey samples analysed. Pollen analysis is an essential tool in identifying the floral types of honeys besides determining their botanical and geographical origins.